Environmental Health Risks Assesment of Human Exposure to Pb Pollution Around Soyoan River, Indonesia - Maddusa, Sri Seprianto; Joseph, Woodford B. S.; Pomantow, Shalom Messy Thessalonika; Asrifuddin, Afnal; Akili, Rahayu H.; Bahrain, Nur Evira Anggrainy (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
The presence of the heavy metal lead (Pb), which accumulates in water and sediment, will enter into the life of organisms which can have a toxic effect on the organisms in it. This study aimed to analyze the health risks of consuming Mujair fish (Oreochromis Mossambicus) which contains the heavy metal Pb in the river flow of Soyoan Village, Ratatotok District, Southeast Minahasa Regency. The research method was descriptive with an environmental health risk analysis (ARKL) approach. Determination of lead levels in fish, water, and sediments used the Atomic Absorption Spectrophotometer method with a graphite furnace. The results showed that the average Pb in Mujair fish was 0.23 mg/kg, the average Pb in water was 1.48 mg/liter, and the average in sediment was 52.98 mg/kg. Pb concentrations in aquatic fish and sediments had exceeded the threshold. The Risk Quotion (RQ) value wasstill below 1 (RQ < 1), meaning that Mujair fish (Oreochromis Mossambicus) in the Soyoan river was still safe for consumption. The ECR value ≤ 10-4 indicated that making risk management was not something that needs to be prioritized. However, the presence of high concentrations was an indicator so that the rate of intake and frequency of exposure can be reduced. In Islamic teachings, it has been explained that damage to the environment due to human actions has an adverse effect on the biota and threatens the surrounding community's health.